Representasi Identitas Komunitas Pada Fans Sepak Bola Madiun Putra - Rizhal Putra Pratama; Nunik Hariyani; Fikri Hasan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines the construction and representation of social identity within two football supporter communities The Mad Mania (TMM) and Great Bull Boys (GBB) as supporters of Madiun Putra football club. Employing a qualitative approach through case study method, data were collected via in-depth interviews with four key informants in 2026. Analysis was conducted using four complementary theoretical frameworks: Tajfel and Turner’s Social Identity Theory (1979), Barthes’ Semiotics (1957), Stuart Hall’s Theory of Representation (1997), and Goffman’s Dramaturgy (1959). Findings reveal that identity in both communities is constructed through three dimensions: social categorization rooted in local and historical values, positive distinctiveness derived from each community’s unique characteristics, and individual identity transformation through membership. Community symbols operate across three semiotic layers denotation, connotation, and myth with the myth of loyalty serving as the most stable value. In the digital context, both communities simultaneously manage two stages (physical and virtual) through fully conscious impression management strategies. The anthem ritual ‘Sang Pahlawan’ proves to be the most powerful mechanism for reproducing collective identity, uniting all elements of Madiun Putra supporters beyond sub-community boundaries. These findings contribute theoretically to the development of multi-theoretical social identity studies in mid-sized-city sporting communities, while offering practical value for club management and supporter communities in leveraging collective rituals to strengthen solidarity and loyalty.